PEMBERITAAN VONIS HAKIM PENYERANG NOVEL BASWEDAN DI MEDIA PENYIARAN (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
The objectives of this study were (1) To find out how the exclusion strategy was in reporting the verdict of the Novel Baswedan attacking judge on Kompas TV 12 to 22 June 2020 edition. until 22 June 2020.The research method used in this research is descriptive qualitative, using a communication approach. Data collection was carried out by conducting observations, documentation and reference tracing. Sources of data used are primary data sources and secondary data sources. The data analysis technique used is critical discourse analysis by Theo Van Leeuwen. Where in this analysis, it is carried out with two elements, namely exclusion and inclusion.The results of this study indicate that journalists are very massive in eliminating actors / actors, in this case Rony Bugis and Rahmat Qadir, in reporting through the exclusion strategy of the nominalization model. In the exclusion strategy, seventeen models of nominalization and four models of passivation were found. Meanwhile, the inclusion strategy found nine differential models, fourteen abstraction models, seven categorization models, one determination model and six assimilation models.The implication of this research is that journalists are bound by a work environment which makes them limited. Then how certain figures / groups are issued and presented in the news depends on the text structure written by journalists.Keywords: Coverage, Judge's Verdict, Novel Baswedan Attacker, Broadcast Media, Critical Discourse Analysis Theo Van Leeuwen